New Zealand Bank Vulnerabilities in International Perspective - Cubero, Rodrigo (IMF Working Papers; Working Paper ;, 2009)
The global financial crisis is creating stress on banking systems across the world through funding and asset quality shocks. This paper combines different stress scenarios, as well as cross-country analysis, to assess New Zealand bank vulnerabilities to the global crisis and the domestic recession. It finds that a sharp worsening of asset quality would be required to reduce bank capital below the regulatory minimum. On the funding side, a disruption to banks' offshore funding may put pressure on the exchange rate, but would not trigger a systemic liquidity problem.